Orally administered fluorescent nanosized polystyrene particles affect cell viability, hormonal and inflammatory profile, and behavior in treated mice. (15th July 2022) - Nikolic, Sandra; Gazdic-Jankovic, Marina; Rosic, Gvozden; Miletic-Kovacevic, Marina; Jovicic, Nemanja; Nestorovic, Natasa; Stojkovic, Petra; Filipovic, Nenad; Milosevic-Djordjevic, Olivera; Selakovic, Dragica; Zivanovic, Marko; Seklic, Dragana; et al.
Abstract: Commercially manufactured or generated through environmental degradation, microplastics (MPs) and nanoplastics (NPs) considerably contribute to environmental pollution. There is a knowledge gap in how exposure to MPs/NPs changes cellular function and affects animal and human health. Here, we demonstrate that after oral uptake, fluorescent polystyrene (PS) nanoparticles pass through the mouse digestive system, accumulate and aggregate in different organs, and induce functional changes in cells and organs. Using cochlear explant as a novel in vitro system, we confirmed the consequences of PS-MP/NP interaction with inner ear cells by detecting aggregates and hetero-aggregates of PS particles in hair cells. The testes of treated males accumulated MPs/NPs in the interstitial compartment surrounding the seminiferous tubules, which was associated with a statistically significant decrease in testosterone levels. Male mice showed increased secretion of interleukins (IL-12p35 and IL-23) by splenocytes while cyto- and genotoxicity tests indicated impaired cell viability and increased DNA damage in spleen tissue. Males also showed a broad range of anxiogenic responses to PS nanoparticles while hippocampal samples from treated females showed an increased expression of Bax and Nlrp3 genes, indicating a pro-apoptotic/proinflammatory effect of PS treatment. Taken together, induced PS effects are also gender-dependent, and therefore, strongly motivate future research to mitigate the deleterious effects of nanosized plastic particles. Graphical abstract: Image 1 Highlights: Orally administrated Polystyrene (PS)-MP/NP pass through mouse digestive system. PS-induced changes in animals' hormonal and immunological profiles. PS particles showed cytotoxic and genotoxic effects in vitro. Orally administrated PS causes changes in animals' behavior which are gender-dependent. PS particles enter both inner and outer hair cells on cochlear explants in vitro.